2009
DOI: 10.1002/jcc.21355
|View full text |Cite
|
Sign up to set email alerts
|

How hot? Systematic convergence of the replica exchange method using multiple reservoirs

Abstract: We have devised a systematic approach to converge a replica exchange molecular dynamics simulation by dividing the full temperature range into a series of higher temperature reservoirs and a finite number of lower temperature subreplicas. A defined highest temperature reservoir of equilibrium conformations is used to help converge a lower but still hot temperature subreplica, which in turn serves as the high-temperature reservoir for the next set of lower temperature subreplicas. The process is continued until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Numerous studies 3843,5153,63,8486 (also SM text and SM Figure VIII), however, have shown that this decapeptide does not have stable conformations. Thus, the behavior observed here can only be attributed to metastable β-hairpin structures with low occurrence probabilities, manifested in our current dynamical trajectories as short-lived conformations.…”
Section: Resultsmentioning
confidence: 98%
“…Numerous studies 3843,5153,63,8486 (also SM text and SM Figure VIII), however, have shown that this decapeptide does not have stable conformations. Thus, the behavior observed here can only be attributed to metastable β-hairpin structures with low occurrence probabilities, manifested in our current dynamical trajectories as short-lived conformations.…”
Section: Resultsmentioning
confidence: 98%
“…These systems were prepared by first removing the solvent, and then the previous solvation and equilibration steps were used to create a final box that contained 6251 water molecules (193 nm 3 volume). The sander module of AMBER and the Multiple-Reservoir Replica Exchange (MRRE) method presented by Ruscio et al 24 were used to achieve a Boltzmann weighted ensemble of 100000 A β 42 structures at the experimental temperature of 287 K, from a 100 ns equilibrated simulation. Details of the MRRE calculations for A β 42 are reported in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The approach that has been applied to biomolecules most often is replica exchange (RE, also called parallel tempering) in which parallel simulations wander among a set of fixed temperature values with swaps governed by a Metropolis criterion [34, 51, 118]. Many variations and optimizations have been proposed for RE (e.g., [8, 11, 26, 57, 64, 67, 9395, 99101, 103, 112, 121]). Closely related to RE is simulated tempering, in which a single trajectory wanders among a set of temperatures [75]; once again, optimizations have been proposed (e.g., [137]).…”
Section: Purely Algorithmic Efforts To Improve Samplingmentioning
confidence: 99%